CLASH: a census of magnified star-forming galaxies at z ~ 6-8 - Bradley, Larry; Zitrin, Adi; Carrasco, Mauricio; Bartelmann, Matthias (Arxiv, 2014)
We utilize 16 band Hubble Space Telescope (HST) observations of 18 lensing clusters obtained as part of the Cluster Lensing And Supernova survey with Hubble (CLASH) Multi-Cycle Treasury program to search for $z\sim6-8$ galaxies. We report the discovery of 204, 45, and 13 Lyman-break galaxy candidates at $z\sim6$, $z\sim7$, and $z\sim8$, respectively, identified from purely photometric redshift selections. This large sample, representing nearly an order of magnitude increase in the number of magnified star-forming galaxies at $z\sim 6-8$ presented to date, is unique in that we have observations in four WFC3/UVIS UV, seven ACS/WFC optical, and all five WFC3/IR broadband filters, which enable very accurate photometric redshift selections. We construct detailed lensing models for 17 of the 18 clusters to estimate object magnifications and to identify two new multiply lensed